(untitled) (Stavební obzor - Civil Engineering Journal, 2023)
Lattice high-molded support can generally be used for cast-in-place support for bridges, but for more than 50 meters of lattice high support, due to the wind, load and other factors, due to the support length and slenderness of the relatively large, relatively light and flexible structure and other characteristics of the role of the wind load is very sensitive. When the lattice high-molded stent construction is used in the typhoon area, it is easy to be damaged by the typhoon, and the structural design of the lattice high-molded stent and the construction of that technology are facing great challenges. In this paper, based on the new construction of a special bridge in Fujian, finite element analysis of four-legged and six-legged lattice bracing is carried out by ANSYS, and the effects of steel pipe diameter, number of columns, longitudinal and transversal spacing of bracing, and diagonal bracing structural parameters on structural performance are analyzed by using the coefficients of buckling stability and the coefficients of critical loading. The results of the study show that the main design variable for displacement sensitivity is the diameter of vertical rod; the main design variable for stress sensitivity is the diameter of diagonal rod; the main design variable for overall stability sensitivity is the diameter of diagonal rod; and the main design variable for overall stability sensitivity of total volume is the diameter of diagonal rod. And the optimal wind resistance parameters are: 4 lattice high-braced columns are selected, the section length should be controlled within 15m, and the total height should not be more than 70m, and the spacing of the columns is controlled between 7m and 8m. This study proposes a set of optimized design process method for wind-resistant lattice structure under the constraints of stiffness, strength and critical load factor, which improves the economy and ensures the reasonableness of the design, and can be used for the design of high-modular lattice bracket in typhoon area.